Modelling grain structures of some carbon steels using voronoi tesselation (2011)
"Modeled grain structures of normalized carbon steels using voronoi tessellation is reported in this work. Three stages of programming were used in modeling the microstructures. The first stage was iteration of the voronoi cells in order to obtain equivalent grain size with experimental specimens. In the second stage, the pearlite phase was introduced using the lever rule represented by a plot of random points. The third layer was modeled to reveal the grain boundaries of the carbon steels. The values of the grain sizes of modeled microstructures showed good agreement with experimental values. The study has shown that the microstructures can be modeled fairly accurately thus enabling a fairly quick export of geometric models on to some other finite element packages for analysis of stress - strain effect on microstructure and generally a stressmicrostructure response could be determined. "